TRAINING ON MAKING HAND SANITIZER BASED ON BAY LEAF EXTRACT (Syzygium polyanthum) - Jhon Patar Sinurat; Reh Malem Br Karo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Hand sanitizer is an alcohol-based hand washing product that can be available in liquid or gel form. Hand sanitizer can kill bacteria and germs on the surface of the hands without having to rinse with water. Bay leaf extract (Syzygium polyanthum) has been known to have antibacterial properties, so it is necessary to make hand sanitizer products based on bay leaf extract. The process of presenting PkM material is carried out using the lecture method assisted by infocus equipment. Meanwhile, the process of making liquid hand sanitizer products is carried out through a demonstration method. The results obtained in this PkM activity are a liquid hand sanitizer product that has a pH of 5, a distinctive bay leaf aroma and hand sanitizer products that are yellowish green or which are usually different from the color of hand sanitizer products in general. Hand sanitizer products are safe to use on the surface of the skin because the pH adjusts to the skin's pH of 4.5 - 6.5. The results of this PkM were also measured based on the post-test conducted on the training participants which showed that as many as 95% of the training participants or as many as 19 people out of 20 participants received an average score of 85 which indicated that the training participants had understood and were able to demonstrate this PkM activity with good. Meanwhile, there was 1 participant or 5% of the participants who got a score of 60, which means they did not understand this PkM activity well.